Electro-click construction of hybrid nanocapsule films with triggered delivery properties. Issue 4 (11th January 2018) - Sciortino, Flavien; Rydzek, Gaulthier; Grasset, Fabien; Kahn, Myrtil L.; Hill, Jonathan P.; Chevance, Soizic; Gauffre, Fabienne; Ariga, Katsuhiko
Abstract : Nanocapsule films composed of hollow PAA/IONPs hybridosomes were covalently assembled in one-pot by electro-click, enabling the encapsulation and triggered release of bodipy. Abstract : Hollow nanocapsules (named Hybridosomes®) possessing a polymer/nanoparticle shell were used to covalently construct hybrid films in a one-pot fashion. The alkyne bearing organic/inorganic Hybridosomes® were reticulated with azide bearing homobifunctional polyethyleneglycol (PEG) linkers, by using an electro-click reaction on F-SnO2 (FTO) electrodes. The coatings were obtained by promoting the Cu(i )-catalyzed click reaction between alkyne and azide moieties in the vicinity of the electrode by the electrochemical generation of Cu(i ) ions. The physicochemical properties of the covalently reticulated hybrid films obtained were studied by SEM, AFM, UV-vis and fluorescence spectroscopy. The one-pot covalent click reaction between the nanocapsules and the PEG linkers in the film did not affect the desirable features of the Hybridosomes® i.e. their hollow nanostructure their chemical versatility and their pH-sensitivity. Consequently, both the composition and the cargo-loading of the Hybridosomes® films could be tuned, demonstrating the versatility of these hybrid coatings. For example, the Hybridosome® films were used to encapsulate and release a bodipy fluorescent probe in response to either a pH drop or the application of an oxidative +1 V potential ( vs. Ag/AgCl) at the substrate. By advancing the field of electro-synthesized films a step further toward the design of complex physicochemical interfaces, these results open perspectives for multifunctional coatings where chemical versatility, controllable stability and a hollow nanostructure are required.